Media Kampanye Sosial Lembaga Swadaya Masyarakat (Save the Children) sebagai Sarana Kekerasan terhadap Anak (Framing Visual dan Kriminologi Konstitutif) - Rina Amelia (Jurnal Kriminologi Indonesia, 2017)
Non-Governmental Organizations (NGO) which work independently from the state in advocating social issues have a crucial role in child protection. Through published campaign medias, NGOs function to build public awareness about problems that children face in their everyday lives. Despite of the fact that NGOs intended to help children, in the same time their campaign medias can also be abusive to children in themselves. In this work, the author use visual framing analysis to see how children are represented in campaign medias, the analyze it criminologically with constitutive criminology. The author found that the pressure to fundraise and competition among NGOs had caused exploitation towards children and attributes that are associated with them. Besides, fundraising and charity which are the convention of the West had their own roles in shaping harmful constructions about children from the East and South.